BRANDING STRATEGY FOR SMALL MEDIUM ENTERPRISES IN THE DIGITAL ERA: A COMMUNITY SERVICE IN CIREBON CITY, WEST JAVA - Adam, Mochammad Riyadh Rizky (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
In the digital age, small and medium enterprises encounter distinct obstacles when it comes to creating and executing successful branding strategies. Similar to how venture capitalists invest in promising startups, small and medium-sized enterprises (SMEs) are now realizing the significance of brand management in driving growth and staying competitive. For small and medium-sized enterprises, a major hurdle is the lack of sufficient financial and human resources to dedicate towards formal branding initiatives. Some small and medium-sized enterprise owners may not fully recognize the value of branding and may not possess the expertise needed to effectively develop and implement a comprehensive branding strategy. Research indicates that small and medium-sized enterprises can greatly profit from implementing effective branding strategies. Branding is a powerful tool for small and medium-sized enterprises (SMEs) to stand out in competitive markets, foster customer loyalty, and improve their public perception and reputation. Building a strong brand has the potential to completely transform a small business into a successful and well-established enterprise. Thus, a seminar and workshop on branding strategy were organized in Cirebon City for small and medium enterprises in Cirebon and the surrounding area. More than 30 persons benefited from this community service. They expect to improve their business.